Photo-destruction of Stromal Fibroblasts Enhances Tumor Response to PDT in 3D Pancreatic Cancer Co-culture Models - Karimnia, Vida (Photochem Photobiol, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal of human cancers. The dismal response of PDAC to virtually all therapeutics is associated, in part, with a characteristically dense fibrotic stroma. This stroma acts not only as a barrier to drug perfusion, but also promotes tumor survival through paracrine crosstalk and biophysical interactions. Photodynamic therapy (PDT) is being explored for PDAC treatment, though the impact of tumor-promoting stromal crosstalk on PDT response in PDAC is not well characterized. The current study assesses the effect of tumor-stroma interactions on response to PDT or chemotherapy in heterocellular 3D co-cultures using PDAC cells and two different fibroblastic cell types (pancreatic stellate cells, PSCs, and a normal human fibroblast cell line, MRC5) embedded in extracellular matrix (ECM). While stromal fibroblasts promote resistance to chemotherapy as expected, PDAC 3D nodules in co-culture with fibroblasts exhibit increased response to PDT relative to homotypic cultures. These results point to the potential for PDT to overcome tumor-promoting stromal interactions associated with poor therapeutic response in PDAC.